2016
DOI: 10.1080/02640414.2016.1143111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emphasising opposition and cooperation on collective movement behaviour during football small-sided games

Abstract: Optimizing collective behaviour helps to increase performance in mutual tasks. In team sports settings, the small-sided games (SSG) have been used as key context tools to stress out the players' awareness about their in-game required behaviours. Research has mostly described these behaviours when confronting teams have the same number of players, disregarding the frequent situations of low and high inequality. This study compared the players' positioning dynamics when manipulating the number of opponents and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 35 publications
5
151
1
2
Order By: Relevance
“…Nevertheless, extreme difficult scenarios probably will produce the contrary effect, and players would not be able to cope with the situation. These results may also be related to that obtained when studying the positioning dynamics of small-sided games [60], as an increase in the number of teammates seemed to promote regularity in spatial organization in AMA teams, although in PRO teams the variation in players’ irregularity ranged from trivial to small. PRO players probably anticipate better the need to optimize collective decision-making.…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, extreme difficult scenarios probably will produce the contrary effect, and players would not be able to cope with the situation. These results may also be related to that obtained when studying the positioning dynamics of small-sided games [60], as an increase in the number of teammates seemed to promote regularity in spatial organization in AMA teams, although in PRO teams the variation in players’ irregularity ranged from trivial to small. PRO players probably anticipate better the need to optimize collective decision-making.…”
Section: Discussionsupporting
confidence: 73%
“…Sampaio et al (2014) further showed that during an inferiority situation during a 5-a-side small sided game the regularity of the distance to the team centroid increased. Goncalves et al (2016) investigated the influence of numerical imbalances between attacking and defending team in small sided games in professional and amateur players. Player numbers varied between 4 versus 3, 4 versus 5, and 4 versus 7.…”
Section: Analysis Of Soccer Tacticsmentioning
confidence: 99%
“…First of all, results were in agreement with O'Donoghue and Cullinane (2011) The quality of opposition is one of the contextual variables that have been widely considered in team sports to evaluate and explain the performance of interested teams against different level of opponents (Gómez, Silva, Lorenzo, Kreivyte, & Sampaio, 2017;Gómez, Lago, et al, 2013;Gonçalves, Marcelino, Torres-Ronda, Torrents, & Sampaio, 2016;Liu et al, 2016) but there is a paucity of investigation in tennis over this topic (Goossens, Kempeneers, Koning, & Spieksma, 2015;O'Donoghue & Cullinane, 2011;Reid et al, 2010). Gosseens et al (2015) grouped the tennis players into 7 categories according to their world ranking and tried to predict the winning probability of male and female players in Grand Slams; Reid et al (2010) used the match statistics of male tennis player tournament from Association of Tennis ( The results of two-step cluster analysis supported the last statement as well in that not all variables in the stronger correlation group were the same ones in every slam, and some of their strengths of correlation varied from one to another.…”
Section: Relationship Between Match Variables and Relative Quality Ansupporting
confidence: 83%